Association of biomass fuel smoke exposure and hypertension among rural women of Bangladesh: A cross-sectional study - Nilima Barman; M Atiqul Haque; A K. M. Fazlur Rahman; M Khalequzzaman; Saidur R Mashreky (Wolters Kluwer Medknow Publications, 2019)
Exposure to biomass fuel smoke has detrimental health effects causing chronic diseases. This study investigated the relationship between biomass fuel smoke exposure and hypertension among the rural Bangladeshi women. A total of 410 women aged 19-60 years were enrolled in this study during April-May 2017 who regularly cooked with biomass fuel in traditional cook stove for the past ≥1 year. Self-reported daily cooking hours and lifetime cooking experience of the participants were recorded, and their blood pressure was measured. Participants' age ≥40 years, parental history of hypertension, body mass index ≥25 kg/m2, and cumulative exposure to biomass smoke were found to be the significant risk factors of hypertension. Every 1 year increase in cumulative exposure to biomass smoke eventually exacerbated the risk of hypertension by 61% (adjusted odds ratio 1.61, 95% confidence interval: 1.16-2.22; P < 0.01). This study provides evidence that long-term exposure to biomass fuel smoke is associated with hypertension.